Chemical and Microbiology Characteristic of Smoked and Seasoned African Catfish Fillet Affected by Canning Processing - Yusuf Kalingga Murda; Amir Husni; Siti Ari Budhiyanti; Ervika Rahayu Novita Herwati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
African catfish (Clarias gariepinus) many cultivated by the farmers, however if not treated quicklydamaged. One treatment that can maintain quality product african catfish is by smoked and canning. Theaim of this study was to determine the chemical and microbiological characteristics of smoked Africancatfish fillet with seasoning packaged cans during storage. Preparation of research carried out by soakingthe African catfish fillet into seasonings and liquid smoke concentration of 10% by immersion for 1minute, and then next process of curing and drying. Products that are ripe weighed 110 g and signedinto cans sized Ø 301x205. Added medium brine concentration 5% and vegetable oil as much as 100ml, a process exhausting and seaming. The last stage is performed a sterilization process (126oC for 20minutes), cooling and incubation (24oC for 2 weeks). Observations deterioration of product quality ofsmoked African catfish fillet with seasoning performed at weeks 0, 2, 4, 6 and 8. Tests conducted includechemical test which includes test TVB, pH and peroxide value and microbiological testing in the formof TPC. The results showed that the combined treatment of the fumigation and the addition of medium(saline 5% and solution of vegetable oil) combined with treatment canning able to maintain productquality of smoked African catfish fillet with seasoning, based TVB, pH, peroxide value and TPC duringstorage.